2004
DOI: 10.1143/jjap.43.5516
|View full text |Cite
|
Sign up to set email alerts
|

Novel Surface Modification of Indium-Tin-Oxide Films Using Ion Implantation for Organic Light-Emitting Diodes

Abstract: Indium–tin–oxide (ITO) films doped using an ion implantation system were used as the anode electrode of organic light-emitting diodes (OLEDs). Changes in the characteristics of the doped ITO films were observed and measured in terms of sheet resistance, Hall mobility, contact angle, roughness, transmittance and work function. Boron dopant was used as an impurity to modify the surface of the ITO films. The depth profile of boron concentration was monitored by secondary ion mass spectrometry (SIMS) as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Moreover, this increase in transmittance is due to the incorporation or adsorption of N 2 into the ITO film that increases the film diffuse transmittance or due to the cooling effect. Choi et al [12] have observed the same trend after B-doping in the ITO film. However, an optical transmittance is closely related to oxygen vacancies, which are associated with free electrons in the ITO films as mentioned earlier.…”
Section: Resultsmentioning
confidence: 52%
“…Moreover, this increase in transmittance is due to the incorporation or adsorption of N 2 into the ITO film that increases the film diffuse transmittance or due to the cooling effect. Choi et al [12] have observed the same trend after B-doping in the ITO film. However, an optical transmittance is closely related to oxygen vacancies, which are associated with free electrons in the ITO films as mentioned earlier.…”
Section: Resultsmentioning
confidence: 52%
“…T ransparent conductive electrodes (TCEs) that simultaneously provide low resistivity (<10 ¹3 ³0cm) and high transmittance (>80%) in the visible region are important components for optoelectronic applications such as solar cells, organic light-emitting diodes, and touch screens. [1][2][3] Until now, various TCE materials such as oxide-based materials [e.g., In 2 O 3 :Sn (ITO), SnO 2 :F (FTO), ZnO:Al (AZO), and SnO 2 :Sb (ATO)], carbon-based materials (e.g., graphene and carbon nanotubes), and metal-based nanowires (NWs) (e.g., Ag NWs and Cu NWs) have been extensively developed. [4][5][6] Among the above-mentioned materials, Ag NWs have recently been proposed as a promising candidate for TCEs because of their low sheet resistance and low extinction coefficient in the visible range.…”
mentioning
confidence: 99%
“…[209,210] Choi et al reported boron doping affects the surface properties of ITO but increases the OLED performance because it influences surface energy, transmittance, sheet resistance, work function and mobility. [211] Zhou et al examined the sand blasting technique for creating surface roughness on OLED substrate, in order to reduce the wave nature of internally generated photons, which could increase the external quantum efficiency from 9% to 11.6%. [212] Hatton et al reported that Silane modified ITO shows better power efficiency as compared to normal ITO surface due to tune the anode work function to the HOMO of HTL.…”
Section: Presence Of Impuritiesmentioning
confidence: 99%